Tinjauan Yuridis Proses Penyelesaian Pelanggaran Kode Etik Notaris Di Kota Samarinda - Aji Titin Roswitha Nursanthy; Alex Chandra; Kadarudin; Eli Tri Kursiswanti (LPPM STIH Awang Long, 2020)
The problems in this research are: a juridical review of the completion of the Notary code of ethics in Samarinda City and the obstacles and solutions to the completion of the Notary code of ethics in Samarinda City. The method used by researchers is a juridical empirical legal approach and the specifications in this study include descriptive analytical. The source and type of data of this research are primary data obtained from field studies by interviewing a notary in Samarinda City. Notaries who commit errors against ethics, appropriateness or moral solutions not only according to the code of ethics alone but also based on statutory regulations. Everything that is not allowed to be done by a notary clearly and is regulated in the regulations. Obstacles in the process of completing the Notary code of ethics in Samarinda City are the large number of Notaries, with a large working area, a lack of awareness of Notaries to comply with the code of ethics, and the provision that the Notary receives is not sufficient while attending education, and overlapping provisions of the code of ethics supervision between the Honorary Council and the Notary Supervisory Council. Meanwhile, for the Supervisory Council, namely the unavailability of a representative secretariat, lack of budget funds to carry out optimal supervision and guidance, lack of government attention / concern, and weak morals/ behavior of Notaries in implementing UUJN and the Notary's Code of Ethics.